Reading Ruth 4 and Leviticus 25:8–55 in the light of the landless and poor women in South Africa: A conversation with Fernando F. Segovia and Ernesto "Che" Guevara - Mtshiselwa, V. Ndikhokele N. (HTS teologiese studies, 2016)
Recent statistics in South Africa shows that women mostly experience poverty as compared to their male counterparts. In the context of the experience of poverty by women, several Old Testament scholars have convincingly explored the theme of poverty in the Hebrew Bible. In her contextual rereading of the Naomi-Ruth Story, Madipoane Masenya (ngwan’a Mphahlele) links the issue of poverty to the theme of land. Also, from the historical-critical and partly, the contextual approach to ancient texts, Esias E. Meyer argues that Leviticus 25:8–55 holds liberating possibilities for women who are invisible in such a text. Based on the argument made by the preceding scholars, firstly, this article argues that in the context from which the texts of Ruth 4 and Leviticus 25:8–55 emerged, some women were both landless and poor. Secondly, it is argued in this article that the context of these texts carries a striking resemblance to the situation of women in modern South Africa, as many women do not own productive land and are poor. Thirdly, this article poses the question: What implications do the ideologies of Ernesto ‘Che’ Guevara and the hermeneutical approach of Fernando F. Segovia to ancient texts bear on the reading of Ruth 4 and Leviticus 25:8–55 in South Africa?Keywords: Book of Ruth; Leviticus; patriarchy; land; poverty; liberation